2020
DOI: 10.1007/s11094-020-02187-x
|View full text |Cite
|
Sign up to set email alerts
|

Current Strategies in Development of New Chromone Derivatives with Diversified Pharmacological Activities: A Review

Abstract: Chromone derivatives possess a spectrum of biological activities. Chromone has been recognized as a privileged structure for new drug invention and development. Substitution pattern of chromone scaffold determines different type of biological activities. The type, number and position of substituents connected to the chromone core play a vital role in determining pharmacological activities. In the present review, we have discussed new chromone derivatives as anticancer, anti-diabetic, antimicrobial, anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 98 publications
(49 reference statements)
0
28
0
1
Order By: Relevance
“…Mechanistically, these compounds caused a cleavage in PARP-1 and activate caspase 7, resulting in morphological changes, such as bleb formation in the treated cells, and a significant increase in the nuclear fragmentation. Considering all the results, these findings demonstrate that these compounds (benzimidazole-piperazine hybrids) exert their cytotoxicity through the apoptotic cell death induction ( Özdemir et al, 2020 ).…”
Section: Mode Of Action As Anti-cancer Agentsmentioning
confidence: 72%
See 2 more Smart Citations
“…Mechanistically, these compounds caused a cleavage in PARP-1 and activate caspase 7, resulting in morphological changes, such as bleb formation in the treated cells, and a significant increase in the nuclear fragmentation. Considering all the results, these findings demonstrate that these compounds (benzimidazole-piperazine hybrids) exert their cytotoxicity through the apoptotic cell death induction ( Özdemir et al, 2020 ).…”
Section: Mode Of Action As Anti-cancer Agentsmentioning
confidence: 72%
“…They evaluated protein–protein interactions in human embryonic kidney 293 (HEK-293) cells using protein-fragment complementation assays (PCA) to detect hidden or not expected biological functions from a wide variety of compounds, belonging to various therapeutic categories. PCA can identify unexpected anti-proliferative effects when using niclosamide, observed in various types of cancer cells, including a human prostate cancer cell (PC-3) ( Samy et al, 2020 ), a human lung cancer cell (A549) ( Özdemir, Turanli, Çalişkan, Arka, & Banoglu, 2020 ), a human pancreatic cancer cell (MiaPaCa) ( Lee, Lee, Sim, & Kim, 2020 ), a human colon cancer cell (LOVO) ( Lee et al, 2020 ), and a human glioblastoma cell (U87MG) ( Arzani et al, 2019 ), with an inhibitory concentration of 50 (IC 50 ) at the mean concentrations of 0.6 µM ( MacDonald et al, 2006 ). Since then, various preclinical studies (L. Chen et al, 2017 , Suliman et al, 2016 , Zhou et al, 2017 ) demonstrated that niclosamide exerts its anti-cancer effects through the inhibition of signaling pathways, including NOTCH, NF-κB, and mammalian target of rapamycin (mTOR).…”
Section: Mode Of Action As Anti-cancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromone is a natural compound present in the diet of humans and animals that has low toxicity to mammalian cells. 11 , 12 Previous studies have also shown that chromone derivatives possess a broad range of biological activities 13 depending on the substitution pattern of the chromone scaffold. 14 Maleimide is an important structural parent nucleus of a class of bioactive molecules and functional materials from Marine natural alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…Chromones are a class of naturally occurring substances, widely distributed throughout nature, which has been recognized as a privileged structure for drug discovery since it has been associated with a variety of biological activities such as antifungal, antidiabetic, antiviral, and anti-hypertensive [7,8]. In addition, several molecules containing the chromone moiety display anti-inflammatory [9] and analgesic [10][11][12] activities.…”
Section: Introductionmentioning
confidence: 99%